Geochemical factors affecting chronological reconstruction of a historical arsenic pollution accident in Lake Qionghai, Southwest of China. Issue 4 (2nd October 2017) - Wang, Xinyu; Shi, Zeming; Ni, Shijun; Xu, Wei; Wang, Ruilin
Abstract : To explore geochemical factors affecting the chronological reconstruction of a historical arsenic pollution accident in Lake Qionghai at southwest of China, heavy metals and radionuclides ( 210 Pbex and 137 Cs) in two sediment cores were sampled and analyzed. Our study revealed that (1) industrialization and urbanization of Xichang since the mid-20 th Century, aggravated soil erosion in the catchment and resulted in a significant and lasting increase in the sedimentation rate of Lake Qionghai; (2) sharp arsenic peaks in two sediment cores recorded an arsenic pollution accident in 2006 in which a large amount of arsenic was discharged into the lake from a chemical plant. Arsenic peaks in sediment cores A and B were dated to 1988 ± 3.5, 2006 ± 3.1, respectively. Only the arsenic peak time in core B: 2006 ± 3.1, agreed with the real pollution accident time of 2006. Linear correlation analysis suggested that arsenic sorption by Fe/Mn minerals and organic materials in sediment core A probably changed the depth distribution of the peak and affected the accuracy of chronological reconstruction. This case study suggested that sorption of heavy metals by Fe/Mn minerals and organic materials should be assessed before the chronological reconstruction of the metal pollution accident in the lake.